PENGARUH PENGGUNAAN MODEL PROJECT CITIZEN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MATA PELAJARAN PPKN - Dini, Sri Fajar; Sulistyarini, Sulistyarini; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of using project citizen learning model towards students’ critical thinking skills in the Civic Education subject in 10th grade of Science II, MAN 1 Pontianak. This is a pre-experimental study with one-group pretest-posttest design. 37 students from class X Science II of MAN 1 Pontianak were taken as the sample. The research instrument used was in the form of an essay with 10 questions. The average score obtained from the pretest and posttest were respectively 32.30 and 79.38. Based on the statistical analysis using SPSS 16.0, the data were normally distributed with the Sig. value greater than 0,05 (0,530 > 0,05). The results of the t-test hypothesis indicate that the sig. value is 0,000 <0,05, whereas the value of decision making referring to the t-table is 19,798> 2.03011; therefore, Ho is rejected and Ha is accepted. Based on the calculation of the effect size value, it was categorized as a strong effect on the value of 5,36 > 1,00. In conclusion, there is an effect in the use of citizen project learning models towards students' critical thinking skills in civic education subject in class X Science II of MAN 1 Pontianak. Keywords: Critical Thinking Skill, Learning Model, Project Citizen.